All ears, all eyes - Jackson, Richard, 1935-; Tillotson, Katherine (New York : Atheneum Books for Young Readers, 2015)
As darkness falls in the forest, animals hoot, chirp, whirr, and bark, lulling drowsy children to sleep.
Keywords: Stories in rhyme; Animal sounds -- Fiction; Forest animals -- Fiction; Bedtime -- Fiction